Analisi Tata Kelola Alokasi Dana Desa: (Studi Kasus Pada Desa Bonjeruk, Kecamatan Jonggat, Kabupaten Lombok Tengah) - Dedi Sukmayadi; Sri Pancawati Martiningsih (Prodi Manajemen Fakultas Ekonomi dan Bisnis Universitas Islam Raden Rahmat Malang, 2025)
This study analyzes the governance of Village Fund allocation in Bonjeruk Village, with an emphasis on the principles of transparency, accountability, and community participation. The method used in this study is qualitative, which includes data collection through in-depth interviews. The findings indicate that the village government has effectively implemented government accounting principles, with financial reports presented transparently and accessible to the community. Community participation in village deliberations has strengthened a sense of ownership and oversight of budget use. However, challenges remain regarding the community's understanding of fund management mechanisms, which can hinder active participation. This study recommends that education and training be provided to the community to improve their understanding of financial reports, and emphasizes the importance of more intensive cooperation between the village government and the community in the decision-making process. These findings are expected to contribute to the development of more efficient and sustainable Village Fund management policies, as well as support the improvement of community welfare in Bonjeruk Village.